Study guides

☆☆

Q: What is 3y plus 4y plus 6 equals 20?

Write your answer...

Submit

Still have questions?

Related questions

3y - 7 + y + 27 = 6y + 20 - 4y Collect terms: 4y + 20 = 2y + 20 Subtract 20 4y = 2y The only way that can happen is if y = 0

2x + 3y = 17 3x + 4y = 24 (2x + 3x) + (3y + 4y) = (17 + 24) 5x + 7y = 41

4y + 4 = 3y - 5 y = -9

(9,2)

6x plus 4y

(-1,-2)

4y + 7 < 3y + 9 4y - 3y < 9 - 7 y < 2

2x + 4y - 5x + 3y = 7y - 3x

-7y + 4y = -3y

6x - 4y

4y -5

10x - 3y + 2x - 4y =(10x + 2x) + (-3y - 4y) =12x - 7y

I don't know whether it's y^2-3y+2+3y-4y-5 or 2y-3y+2+3y-4y-5, so I'll do both.y^2-3y+2+3y-4y-5y^2+(-3y+3y-4y)+(2-5); group them togethery^2+(-4y)+(-3)y2-4y-3OR2y-3y+2+3y-4y-5(2y-3y+3y-4y)+(2-5); group them together(-2y)+(-3)-2y-3

x = 5, y = -1

If y + 3y + 10 = 70, then 4y + 10 = 70, and 4y = 60. We then find that y = 60/4 = 15.

x=-2, y=2

-3y

10x+2x-3y-4y=12x-7y

If: 2x-3y = -15 and x = 4y Then: x = -12 and y = -3

4y + 7 - y = 10 + 3y My next step is to combine the y's on the left, 3y + 7 = 10 + 3y If I then subtract 3y from both sides I obtain 7 = 10 which is not a true statement. Hence, the equation that you presented is invalid.

The ordered pair is (-1, -2).

7y = 3y - 12 4y = -12 y = -3

7(3y-2)-(-4y+9)

It is the same as: 6x+4y

4y-3y = 1